Life in the intertidal: Cellular responses, methylation and epigenetics. (5th March 2018) - Clark, Melody S.; Thorne, Michael A. S.; King, Michelle; Hipperson, Helen; Hoffman, Joseph I.; Peck, Lloyd S.
Abstract: Phenotypic plasticity is essential for the persistence of organisms under changing environmental conditions but the control of the relevant cellular mechanisms including which genes are involved and the regulation of those genes remains unclear. One way to address this issue is to evaluate links between gene expression, methylation and phenotype using transplantation and common garden experiments within genetically homogeneous populations. This approach was taken using the Antarctic limpet Nacella concinna . In this species, two distinct phenotypes are associated with the intertidal and subtidal zones. The in situ gene expression and methylation profiles of intertidal and subtidal cohorts were directly compared before and after reciprocal transplantation as well as after a common garden acclimation to aquarium conditions for 9 months. Expression profiles showed significant modulation of cellular metabolism to habitat zone with the intertidal profile characterised by transcription modules for antioxidant production, DNA repair and the cytoskeleton reflecting the need to cope with continually fluctuating and stressful conditions including wave action, UV irradiation and desiccation. Transplantation had an effect on gene expression. The subtidal animals transplanted to the intertidal zone modified their gene expression patterns towards that of an intertidal profile. In contrast, many of the antioxidant genes were still differentially expressed in the intertidal animals several weeks after transplantation into the relatively benign subtidal zone. Furthermore, a core of genes involved in antioxidation was still preferentially expressed in intertidal animals at the end of the common garden experiment. Thus, acclimation in an aquarium tank for 9 months did not completely erase the intertidal gene expression profile. Significant methylation differences were measured between intertidal and subtidal animals from the wild and after transplantation, which were reduced on common garden acclimation. This suggests that epigenetic factors play an important role in physiological flexibility associated with environmental niche. A plain language summary is available for this article. Abstract : Plain Language Summary